Система автоматичного керування частотою обертання двигуна приводу верстата з ЧПК - Горелік, Ілля Ігорович; Gorelik, Ilya (ЦНТУ, 2023)
Основна задача бакалаврської роботи автоматизувати систему контролю приводу подачі оброблювального центру за принципом відхилення вихідної величини та довести техніко-економічні показники. Використовуючи модернізовану систему керування приводу головного руху оброблювального центру верстату МС 032, покращено управління верстатом, підвищено точність роботи, а отже підвищено якісні та економічні показники процесу обробки деталей.The main task of the diploma project is to automate the control system of the feed drive of the processing center according to the principle of deviation of the initial value and to prove technical and economic indicators. Using the modernized control system of the main drive of the machining center of the MS 032 machine, the control of the machine has been improved, the accuracy of work has been increased, and therefore the quality and economic indicators of the processing of parts have been increased.
The system of automatic control of the frequency of rotation of the engine of the machine tool with a CNC
Keywords: частота обертання; двигун верстата; система автоматичного керування; rotation frequency; machine engine; automatic control system